Siyasah Dusturiyyah sebagai Sistem Perpolitikan dalam Al-Qur’an - Salman Abdul Muthalib; Muhammad Faizur Ridha bin Mohd Pauzi (TAFSE: Journal of Qur'anic Studies, 2019)
Siyasah dusturiyyah so far has not been revealed in detail. In the world history stage, it can be seen that the good or bad of a country depends on the system of government. The Qur'an has clearly stated the necessity of government. Allah SWT ordered the Messenger of Allah to get used to and train himself in government affairs. Thus, to find the ideal of Islam in the process of administering the government, the title of the thesis on "Interpretation of the Siyāsah Dusturiyāh Verses (Study of Government Systems)" is very interesting to study. Data analysis was carried out using thematic (Maudhu'ï). In the thematic method, all related verses are collected, then studied in more depth from various aspects related to them. This method is also supported by arguments or truths that can be justified scientifically and rationally. Based on the method used, the Qur'an explains that leadership in the dusturiyah siyāsah can be adapted to every era. Leadership in Islam is natural for every human being as well as motivates Islamic leadership. Humans are entrusted by Allah SWT to be the caliph to lead the people in religion and the world, also regulate the people and guard religion and politics. The system of government referred to in the Qur'an consists of five: the Imamate, the People and Their Obligations, Bai'at, Ahl al-Hall Wa al-Aqd, and Wizarah. Siyasah dusturiyyah selama ini belum terungkap secara terperinci. Dalam pentas sejarah dunia dapat dilihat bahwa baik buruknya negara tergantung dengan sistem pemerintahan. Alquran secara tegas telah menetapkan keharusan adanya pemerintahan. Allah Swt memerintahkan Rasulullah Saw untuk membiasakan dan melatih diri dalam urusan kepemerintahan. Dengan demikian untuk menemukan idealitas Islam dalam proses penyelenggaraan pemerintahan, maka judul skripsi tentang “Penafsiran Ayat-Ayat Siyāsah Dusturiyāh (Kajian Sistem Pemerintahan)” sangat menarik untuk dikaji. Analisis data yang dilakukan dengan menggunakan tematik (Maudhu’ï). Dalam metode tematik semua ayat yang berkaitan dikumpulkan, kemudian dikaji secara lebih mendalam dari berbagai aspek yang berkaitan dengannya. Dalam metode ini juga didukung dengan dalil-dalil atau kebenaran yang dapat dipertanggungjawabkan secara ilmiah dan rasional. Berdasarkan metode yang digunakan, Alquran menjelaskan bahwa kepemimpinan dalam siyāsah dusturiyāh dapat disesuaikan dengan setiap zaman. Kepemimpinan dalam Islam merupakan fitrah bagi setiap manusia sekaligus memotivasi kepemimpinan yang Islami. Manusia di amanahi Allah Swt untuk menjadi khalifah untuk memimpin umat dalam agama dan dunia, juga mengatur umat serta menjaga agama dan politik. Sistem pemerintahan yang disebut di dalam Alquran terdiri dari lima: yaitu Imamah, Rakyat dan Kewajibannya, Bai’at, Ahl al-Hall Wa al-Aqd, dan Wizarah.